Educational inputs and economic development in end-of-nineteenth-century Prussia - Ruth Schueler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
Which role did educational investments play for economic development? Using data on schooling quantity and quality provided by the first and second Prussian census on primary schools and two measures capturing the high and the low end of the income distribution allows applying a value-added approach for industrializing West Prussia. I find that educational investments and in particular teacher unit costs increase income tax per capita substantially while day laborer wages are unaffected. Exploring the sectoral composition of the economy, it is hypothesized that the rising income stems from a shift to higher skilled and higher paid occupations.
Keywords: N33; I22; H52; 330; Educational economics; economic development; input output analysis; expenditures; Prussian economic history